Multimodal OCT Reflectivity Analysis of the Cystoid Spaces in Cystoid Macular Edema - Farci, Roberta (Biomed Res Int, 2019)
PURPOSE: To compare and evaluate images of macular cysts with different degrees of reflectivity (from gray to black signal) as observed in B scan spectral domain OCT (SDOCT) and EnFace OCT with decorrelation signal obtained with OCT-angiography (OCTA) in eyes with cystoid macular edema (CME) secondary to diabetic retinopathy (DR) and retinal vein occlusion (RVO). METHODS: Images from 3033 patients affected by CME secondary to diabetes or RVO examined OCTA (Optovue XR Avanti, Optovue, USA) at the University Eye Clinic of Créteil, Hôpital Intercommunal, France, and at the University Eye Clinic of Cagliari, “San Giovanni di Dio” Hospital, Italy, were retrospectively examined. The deep capillary plexus OCTA images and the corresponding EnFace OCT images, both acquired with the same automatic segmentation, had been overlapped to compose RGB color images as red and green channels, respectively, using ImageJ software (National Institutes of Health, Bethesda, MD). Afterward, linear regions of interest were traced on the color images to obtain the profiles of OCTA and EnFace gray values. Number of pixels, mean gray value and standard deviation of the area traced in OCT-A, and EnFace image were analyzed and statistically correlated. Data were exported to Excel to create the plots. RESULTS: 94 patients with DME and 27 patients with RVO showed intraretinal macular cystoid spaces with similar homogeneous, gray-looking content; 73 patients with DME and 113 patients with RVO showed macular cystoid spaces with homogeneous, black-looking content, as observed at SD-OCT, EnFace and OCTA scans. Interestingly, the limits of macular cystoid spaces were clearly detectable with OCTA. The analysis of red and green profiles demonstrated a clearly visible overlap between average OCTA and EnFace signal observed around cystoid spaces that could be attributed to a relationship between the dynamic vascularization and the structural density of the tissue. CONCLUSIONS: This is the first investigation that characterizes and correlates OCTA and EnFace signals on images of macular cystoid spaces in DR and RVO. The low intensity OCTA signals observed inside cystoid spaces raise a relevant question about their nature, as to whether they are due to the presence of corpusculated material pouring out from bloodocular-barrier or they should be considered OCTA artifacts.